Caracterización bioquímica de lipasas producidas por hongos termotolerantes en fermentación en medio sólido - Hernández Rodríguez, Blanca Elizabeth (Universidad Autónoma Metropolitana, 2012)
Filamentous fungi are one of the most important lipases sources for industrial applications since these are extracellular enzymes which make easier their recuperation from the fermentation medium. However, the activity and stability of biocatalysts are the main criteria for their incorporation into the catalytic systems, especially when the reaction medium is an organic solvent and the temperature process is above 40 oC. By the above, the objective of the present work was to study the production of lipases by filamentous thermotolerant fungi and evaluate their stability in function of temperature and organic solvents polarity. Two immobilization methods were subsequently applied in order to improve the activity, stability and selectivity of lipases in processes of synthesis of molecules with biological activity. Finally, some of the structural properties of the lipases were analyzed by mass spectroscopy.Some studies of lipases production, by six strains of thermotolerant fungi (Rhizopus sp.) and one thermophilic strain (Rhizomucor sp.) were carried on, in solid state fermentation during the first experimental stage. The enzymatic activity of the biocatalysts produced by two strains of thermotolerant fungi Rhizopus microsporus var. tuberosus (74.0  7.0 U/gms, strain 19) and Rhizopus microsporus var. chinensis (72.4  5.7 U/gms, strain 43a) were comparable to the activity shown by the commercial lipase Lipozyme® RM IM of Novozymes (118.12  1.0 U/gms). In the second experimental phase the stability of lipases, naturally immobilized in the dehydrated fermented solids (biocatalysts) were evaluated as a function of the organic solvent polarity and temperature. In this study, the use of the organic solvents dipole moment together with their classification based on the functional groups (non-polar, polar protics and polar aprotics) allowed to establish four different relative activity profiles with the seven evaluated biocatalysts. All the evaluated biocatalysts shown an elevated relative activity (greater than 90 %) in polar aprotic solvents (acetonitrile, acetone and ethyl acetate) compared to the unexposed biocatalysts to organic solvents (100% relative activity). However, in protic polar solvents (ethanol and i-propanol) the activity was considerably reduced (less than 40%). Furthermore, after incubation in i-amyl alcohol, the lipase activity of the biocatalysts which contain the strains Rhizopus microsporus var. tuberosus (L-19) and Rhizopus microsporus var. chinensis (L-43a) increased in the synthesis of ethyl oleate 3.36 and 1.46 fold, respectively. The activity of L-19 was also increased after incubation in toluene (2.0 fold), i-propanol (1.5 fold) and acetonitrile (1.3 fold) at temperatures of 30 ºC and 50 ºC. These results suggest that the biocatalyst L19 and L-43 could be used in several reactions catalyzed by lipases in organic mediums. In the third experimentally step the enantioselectivities (E) of lipases in the reactions of hydrolysis were evaluated. The lipases tested were produced by the strains Rhizopus homothallicus var. rhizopodiformis (13a), Rhizopus microsporus var. tuberosus (19) and Rhizopus microsporus var. chinensis (43a) immobilized on Octyl-agarose (interfacial adsorption) and MANAE-glutaraldehyde (multipuntual covalent bond). The chiral substrates used for the hydrolysis reactions were acid ()-2-O-butyryl-2-phenylacetic [()-OBFA] and ()- ethyl-2-hydroxy-4-phenylbutyrate [()-HFBE]; for the asymmetric hydrolysis the prochiral substrates used were di-n-methyl [DMFG] and di-n-ethyl-phenyl-glutarate [DEFG]. The results corresponding to hydrolysis of ()-OBFA presented enantioselectivity values (E) of 25 and 5 for the lipase derivatives 19 MANAE-glutaraldehyde and octyl-agarose, respectively. For the lipases 13a and 43a, the enantioselectivities were modified through the process of immobilization and it was observed a remarkable increase in the aforementioned property (E=) towards the enantiomer (S) in both derivatives Octyl agarose. This indicates that the acquired conformation by the active site of the enzyme, when this is adsorbed on the hydrophobic surface, limits the entrance to the enantiomer (R). In the hydrolysis of the substrate ()-HFBE it was not observed a significant effect of the immobilization type and the enantioselectivity. With respect to the asymmetric hydrolysis it was observed a remarkable change in the enantioselectivity of the lipase 19, when it was immobilized on the MANAE-glutaraldehyde. A value of E= (S) was obtained. The derivatives from the strains 13a and 43a showed a value of E≈7 (R) and a contrary selectivity of the strain 19. Finally, as a result of the protein analysis by mass spectroscopy it was found a peptide in the band corresponding to the strain 43a with a high index of reliability (Score > 95) in correspondence to a protein produced by Rhizopus stolonifer. The peptide presented a high homology with the protein of thermal shock Hsp70 protein 1 of Rhizopus stolonifer whose primary structure and functional properties correspond with a chaperone. This is in agreement with previous studies about mechanism of lipase secretion by the genus Rhizopus, which demonstrate the synthesis of these enzymes as pro-peptides that work as intramolecular chaperones. Besides, five potential consensus sequences for N-glicosylation in the protein and that not contribute to the thermoestability of the enzyme were identified. The results obtained in this study suggest that the biocatalysts produced in solid state fermentation by the strains 13a, 19 and 43a present technological and economic advantages for use in various catalytic processes in both aqueous systems (hydrolysis reactions) and nonaqueous (synthesis reactions). In addition, enzymatic derivatives prepared by two lipases immobilization methods (Octyl-agarose interfacial adsorption and MANAE-glutaraldehyde multipuntual covalent bond) may be employed in catalytic processes for biosynthesis of important biomolecules to the pharmaceutical industry, such as (S)-mandelic acid, (S)-2- hydroxy-4-phenylbutanoic acid, (S)-n-methyl-phenylglutarate and (S)-n-ethyl-phenylglutarate.; Los hongos filamentosos son una de las fuentes más importantes de lipasas para aplicaciones industriales, ya que las producen generalmente de forma extracelular, facilitando así su recuperación a partir del medio de fermentación. Sin embargo, la actividad y la estabilidad de los biocatalizadores, son los criterios que determinan su incorporación a los sistemas catalíticos, sobre todo, si el medio de reacción consiste en solventes orgánicos y el proceso se lleva a cabo a temperaturas mayores a 40 °C. Por lo anterior, el objetivo del presente trabajo, fue producir lipasas por hongos filamentosos termotolerantes y evaluar su estabilidad en función de la temperatura y la polaridad de los solventes orgánicos. Posteriormente, se aplicaron dos métodos de inmovilización con el propósito de mejorar la actividad, estabilidad y selectividad de las lipasas en procesos de síntesis de moléculas con actividad biológica, y finalmente se analizaron algunas de las propiedades estructurales de las mismas por espectrometría de masas.Durante la primera etapa experimental, se realizaron estudios sobre la producción de lipasas en fermentación en medio sólido (FMS) por seis cepas de hongos termotolerantes (Rhizopus sp.) y una cepa termófila (Rhizomucor sp.). Las actividades enzimáticas de los biocatalizadores producidos por dos cepas de hongos termotolerantes, Rhizopus microsporus var. tuberosus (74.0  7.0 U/gms, cepa 19) y Rhizopus microsporus var. chinensis (72.4  5.7 U/gms, cepa 43a) fueron comparables a la obtenida por la lipasa comercial Lipozyme® RM IM de Novozymes (118.12  1.0 U/gms). En la segunda etapa experimental, se evaluó la estabilidad de las lipasas inmovilizadas de manera natural en los sólidos fermentados deshidratados (biocatalizadores) en función de la polaridad de los solventes orgánicos y de la temperatura. En este estudio, el uso del momento dipolar de los solventes orgánicos junto con su clasificación en base a los grupos funcionales (no-polares, polares próticos, polares apróticos) permitió establecer cuatro diferentes perfiles de actividad relativa con los siete biocatalizadores evaluados. En comparación a los biocatalizadores no expuestos a solventes orgánicos (100% actividad relativa), todos los biocatalizadores mostraron una elevada actividad relativa (mayor al 90%) en solventes polares apróticos (acetonitrilo, acetona y acetato de etilo), mientras que en solventes polares próticos (etanol e i-propanol), la actividad se redujo considerablemente (menor al 40%). Además, después de incubar a 25°C los biocatalizadores de las cepas Rhizopus microsporus var. tuberosus (L-19) y Rhizopus microsporus var. chinensis (L-43a) en alcohol i-amílico, se incrementó la actividad lipasa en la síntesis de oleato de etilo 3.36 y 1.46 veces, respectivamente. La actividad de L-19 también se incrementó después de incubar en tolueno (2.0 veces), ipropanol (1.5 veces) y acetonitrilo (1.3 veces) a temperaturas de 30 ºC a 50 ºC. Estos resultados sugieren que los biocatalizadores L-19 y L-43a pueden ser empleados en diversas reacciones catalizadas por lipasas en medios orgánicos.En la tercera etapa experimental, se evaluó la enantioselectividad (E) de las lipasas producidas por las cepas Rhizopus homothallicus var. rhizopodiformis (13a), Rhizopus microsporus var. tuberosus (19) y Rhizopus microsporus var. chinensis (43a) inmovilizadas sobre Octil-agarosa (adsorción interfacial) y MANAE-glutaraldehído (unión covalente multipuntual) en las reacciones de hidrólisis de los sustratos quirales ácido ()-2-O-butiril-2- fenilacético [()-OBFA] y ()-2-hidroxi-4-fenilbutirato de etilo [()-HFBE], así como en la hidrólisis asimétrica de los sustratos pro-quirales di-n-metil [DMFG] y di-n-etil-fenil-glutarato [DEFG]. Los resultados que corresponden a la hidrólisis de ()-OBFA, muestran valores de enantioselectividad (E) de 25 y 5 para los derivados de la lipasa 19 MANAE-glutaraldehído y Octil-agarosa, respectivamente. Para las lipasas 13a y 43a, la enantioselectividad se modificó a través del proceso de inmovilización y se observó un notable incremento en dicha propiedad (E=) hacia el enantiómero (S) en ambos derivados Octil-agarosa. Esto indica que la conformación adquirida por el sitio activo de la enzima cuando ésta es adsorbida a la superficie hidrofóbica del soporte limita la entrada del enantiómero (R). En la hidrólisis del sustrato ()- HFBE, no se observó un efecto significativo del tipo de inmovilización sobre la enantioselectividad. Y en lo referente a la hidrólisis asimétrica, se observó un cambio notableen la enantioselectividad de la lipasa 19 al inmovilizar sobre el soporte MANAE-glutaraldehído obteniendo un valor E= (S). Los derivados de las cepas 13a y 43a presentaron un valor de E≈7 (R) y una selectividad contraria al derivado de la cepa 19. En la cuarta etapa experimental, como resultado del análisis de proteínas por espectrometría de masas, se encontró un péptido en la banda correspondientes a la cepa 43a con un alto índice de confiabilidad (Score > 95) en la correspondencia a una proteína producida por Rhizopus stolonifer, el cual presentó una alta homología con la proteína de choque térmico Hsp70 proteína 1 de Rhizopus stolonifer, cuya estructura primaria y propiedades funcionales corresponden al de una chaperona. Esto coincide con estudios previos sobre mecanismos de secreción de lipasas por el género Rhizopus, los cuales evidencian la síntesis de estas enzimas como pro-péptidos que actúan como chaperonas intramoleculares. Además, se identificaron cinco secuencias consenso potenciales de N-glicosilación en la proteína, que posiblemente contribuyan con la termoestabilidad de la enzima. Con base a los resultados obtenidos en este trabajo se sugiere que los biocatalizadores producidos en fermentación en medio sólido por las cepas 13a, 19 y 43a presentan ventajas tecnológicas y económicas para su empleo en diversos procesos catalíticos tanto en sistemas acuosos (reacciones de hidrólisis) como no acuosos (reacciones de síntesis). Además, los derivados enzimáticos obtenidos por dos métodos de inmovilización de lipasas (adsorción interfacial -Octil-agarosa- y unión covalente multipuntual -MANAE-glutaraldehído-) pueden emplearse en procesos catalíticos de síntesis de biomoléculas de importancia para la industria farmacéutica, tales como: (S)-Ácido mandélico, (S)- ácido-2-hidroxi-4-fenilbutanoico, (S)-nmetil-fenilglutarato y (S)-n-etil-fenilglutarato.